2020
DOI: 10.55713/jmmm.v30i1.575
|View full text |Cite
|
Sign up to set email alerts
|

The water permeability properties of re-vibrated lightweight concrete

Abstract: Re-vibration of sequential layers of relatively deep structural members after a particular time harms the strength and water permeability properties of the concrete. The harmful effects can be observed in lightweight concrete due to the floating tendency of lightweight aggregate. In this experimental study, the influence of adding retarder plasticizer and silica fume on water permeability properties of re-vibrated lightweight concrete was investigated. The effects of re-vibration at different time lags on comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The mixing and batching procedure used for the reference mixtures was followed consistently to ensure efficiency, uniformity, and homogeneity in the mixtures [10]. The materials were first weighed and prepared.…”
Section: Casting Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The mixing and batching procedure used for the reference mixtures was followed consistently to ensure efficiency, uniformity, and homogeneity in the mixtures [10]. The materials were first weighed and prepared.…”
Section: Casting Proceduresmentioning
confidence: 99%
“…In an experimental study conducted by Kassim [10], the impact of adding silica fume on the water permeability characteristics of revibrated lightweight concrete was analyzed. The study found that even though the mixes were revibrated before the cement's final setting, the incorporation of silica fume resulted in increased compressive strength and reduced permeability for all of the mixtures.…”
Section: Introductionmentioning
confidence: 99%